Sensory Amplitude Electrical Stimulation via Sock Combined With Standing and Mobility Activities Improves Walking Speed in Individuals With Chronic Stroke: A Pilot Study - Lopez-Rosado, Roberto; Kimalat, Andrea; Bednarczyk, Matthew; Sullivan, Jane E. (Frontiers in Neuroscience, 2019)
Objective: To determine if sensory amplitude electrical stimulation (SES) delivered via sock electrode combined with standing and mobility activities improved gait speed, sensation, balance, and participation in chronic stroke. It was hypothesized that SES would enhance the effectiveness of exercise, resulting in reduced impairment and improved function. Design: Case Series. Setting: Home-based intervention. Participants: Thirteen adults (56.5 + 7.84 years old) with chronic stroke (8.21 + 4.36 years post) and hemiparesis completed the study. Participants were community ambulators. Intervention: Participants completed 6 weeks of self-administered SES delivered via sock electrode concurrent with standing and mobility activities for a minimum of 5 days/week for 30-min, twice daily. Outcome Measures: Berg Balance Scale (BBS), Stroke Rehabilitation Assessment of Movement—LE subscale (STREAM), 10 Meter Walk Test (10 MWT), Activities-Specific Balance Confidence Scale (ABC), Stroke Impact Scale (SIS), Perceptual Threshold of Electrical Stimulation (PTTES), and Monofilament testing were administered at pre-test, post-test, and 3-month follow up. Results: Baseline sensory scores and change scores on functional outcomes were analyzed using Pearson Product-Movement Correlation Coefficients, Friedman test, and Linear mixed models. There was a significant change with 10 MWT self-selected pace (Friedman's p = 0.038). Pre-post intervention changes in other outcome measures were not significant. According to the Cohen's effect size classification, there were medium effect sizes for both the STREAM-LE and Monofilaments. Conclusion: The use of home-based SES via sock electrode combined with standing and mobility activities may contribute to improve gait speed in chronic stroke.